Model Komunikasi City Branding dalam Pengembangan Wisata Bahari Pulau Terintegrasi di Kota Sibolga - Tanjung, Irwan Syari; Tanjung, Hasrudy; Tenerman, Tenerman (PERSPEKTIF, 2024)
Sibolga City has great potential in the development of integrated island marine tourism, but still faces challenges in attracting an optimal number of tourist visits. This study aims to identify the factors that cause low tourist visits on the integrated island and design an online media-based city branding communication model to increase the number of tourist visits. The research method used is qualitative descriptive with data collection through interviews, observation, and document tracing. The results showed that the development of integrated island marine tourism requires attention to aspects of tourist attraction, facilities, and institutional additional services. This research recommends the use of online media and innovative branding strategies to improve the image of Sibolga marine tourism and increase tourist participation in tourism promotion through social media. Thus, this research contributes to strengthening the tourism potential of Sibolga city and increasing tourist visits to the integrated island.